2006
DOI: 10.1086/499261
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Weak MgiiAbsorbers at Redshift 〈z〉 = 1.78

Abstract: The exact nature of weak Mg ii absorbers [those with W r (2796) < 0:3 8] is a matter of debate, but most are likely related to areas of local star formation or supernova activity outside of giant galaxies. Using 18 QSO spectra obtained with the Ultraviolet and Visual Echelle Spectrograph (UVES) on the Very Large Telescope (VLT), we have conducted a survey for weak Mg ii absorbers at 1:4 < z < 2:4. We searched a redshift path length of Áz ¼ 8:51, eliminating regions badly contaminated by atmospheric absorption … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…While intermediate-strength systems show no evolution to within fairly strong limits over the large range 0:5 P z P 2 ( Fig. 5; also see NTR05 for discussion), there is evidence that the incidence of weak systems exhibits a significant decrease above z % 1 (Lynch et al 2006). It should also be noted, however, that most single-cloud systems have W k2796 0 < 0:1 8 (the limit of this study).…”
Section: Population-dependent Evolutionmentioning
confidence: 54%
“…While intermediate-strength systems show no evolution to within fairly strong limits over the large range 0:5 P z P 2 ( Fig. 5; also see NTR05 for discussion), there is evidence that the incidence of weak systems exhibits a significant decrease above z % 1 (Lynch et al 2006). It should also be noted, however, that most single-cloud systems have W k2796 0 < 0:1 8 (the limit of this study).…”
Section: Population-dependent Evolutionmentioning
confidence: 54%
“…(following Churchill et al 1999), we found 28 systems in a redshift path ∆z = 13.6 (see also Lynch et al 2006). We also examined the sample of Churchill et al (1999) observed with HIRES at Keck, in the same redshift range, at a similar resolution, but in general at a lower signal-to-noise ratio.…”
Section: Comparison With Weak Mg II Systemsmentioning
confidence: 69%
“…In addition, Lynch et al (2006) and Narayanan et al (2007) discovered an evolution in the redshift number density (dN /dz) of weak Mg ii absorbers over the interval 0:4 < z < 2:4. The dN /dz was found to peak at z ¼ 1:2, and subsequently decline (from a no-evolution trend) toward higher redshift.…”
Section: à3mentioning
confidence: 99%